Power distribution control strategy of grid-forming converters based on adaptive virtual impedance (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
Aiming at the challenges of power distribution imbalance and stability caused by uneven impedance and dynamic load changes during parallel operation of grid-forming converter ( GFC ) in an islanded microgrid, it is difficult to achieve accurate power distribution by using the traditional droop control strategy. In order to improve the accuracy of power allocation, this paper proposes a power allocation control strategy based on adaptive virtual impedance. The power allocation strategy based on this method calculates the status information entropy ( SIE ) as a key feature to quantify the global power imbalance state of the system by obtaining the voltage situation information of the point of common coupling ( PCC ). Then, taking the entropy value as the sensing input, a piecewise linear mapping rule between information entropy and virtual impedance parameters is proposed to dynamically adjust the system damping and droop coefficient, which ensures the high-precision power distribution under the condition of unknown line impedance.
Keywords: Grid Forming, Virtual Impedance, Power Distribution, Parallel Converter.